PENGARUH MACAM BIOCHAR DAN PUPUK KIMIA MAJEMUK PADA PERTUMBUHAN DAN PRODUKSI TANAMAN BAWANG MERAH (Allium ascalonicum L.) - Anam, Choirul; Ramadhani, Adelia Frizka; Istiqomah, Istiqomah (AGRORADIX : Jurnal Ilmu Pertanian, 2024)
Allium ascalonicum L., often known as shallot, is a highly valued and useful horticultural plant. The soil amendment used is biochar. The balanced fertilizer used is a compound chemical fertilizer. The aim of the research is to understand the effect of biochar and compound chemical fertilizer on the growth and production of shallot plants (Allium ascalonicum L.). This research applies the Factorial Randomized Group Design (RAK) method, each of which is formed from two parts and divided into three levels. Biochar and compound chemical fertilizer are the first and second factors. There were three forms of biochar used: without biochar (control) (B1), rice husk biochar (B2), and coconut shell biochar (B3). Compound chemical fertilizers used: Phonska (M1), Mutiara (M2), and Saprodap (M3). Parameters observed during the vegetative phase include plant height and number of leaves. The number of tubers per sample, wet weight of tubers per plot, dry weight of tubers per plot and per hectare are some of the input harvest parameters. Observational data were analyzed using Fisher’s variance (F test level 5%). If there is a significant difference, the Least Significant Difference Test (BNT 5%) is applied. Treatment without biochar (control) and Mutiara compound chemical fertilizer was able to increase the growth and production of shallot plants.